Factors Affecting the Sustainability of Information Technology Projects in Public Organizations: The Case of the Ethiopian Revenues and Customs Authority - Akemachew, Abay (African Journal of Leadership and Development, 2020)
The project environment in the 21st century is characterized by a high level of uncertainties mainly as a result of faster technological changes, involvement of various stakeholders with their diverse and ever-changing needs and requirements, and required an outlay of huge amounts of money. Therefore, in the dynamic environment, satisfying the needs and requirements of project stakeholders sustainably is challenging. The study aims to investigate the factors that affect the sustainability of information technology (IT) projects in the Ethiopian Revenue and Customs Authority (ERCA). In order to meet the objectives of the study, a descriptive research design and mixed research approach were employed. The result of the study has shown that the alignment of the introduced systems with the vision and mission of the Authority, the establishment of a department that can provide technical support for users and others are the identified factors that positively influence the sustainability of IT projects in ERCA. Some of the factors that negatively affect the sustainability of the products of IT projects include the absence of organizational policy and guidelines which can govern the utilization of IT, incompatibility of the existing technologies with some of the national proclamations and so forth. However, it is difficult to say as IT projects introduced to administer tax in ERCA are sustainable to some extent rather they are “challenged projects.” Therefore, to address the identified gaps, designating organizational policy and guidelines to govern the products of the IT projects scientifically is critically needed by ERCA. Also, the Authority should work with the concerned federal stakeholders to create alignment between the national frameworks and the introduced IT systems.